Isoscaling and the high-temperature limit - Dorso, Claudio Oscar (2008)
This study shows that isoscaling, usually studied in nuclear reactions, is a phenomenon common to all cases of fair sampling. Exact expressions for the yield ratio R21 and approximate expressions for the isoscaling parameters α and β are obtained and compared to experimental results. It is concluded that nuclear isoscaling is bound to contain a component due to sampling and, thus, a word of caution is issued to those interested in extracting information about the nuclear equation of state from isoscaling. © 2008 The American Physical Society.